Manajemen “Kurikulum Langit” dalam menguatkan pendidikan karakter siswa - Ivan Supangat; Nan Rahminawati; Bambang Saiful Ma'arif (Fakultas Tarbiyah dan Keguruan dan UPT Publikasi Ilmiah (Universitas Islam Bandung), 2024)
The purpose of this study was to determine the management of a special curriculum in an educational institution in strengthening students' character. Programmed management will be able to optimize educational institutions in achieving learning goals to produce students with positive character. The location of the study was at SD Juara, East Jakarta. The special curriculum that was implemented was named